A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
anonymous
 3 years ago
Solve for x: 3(x + 1) = −2(x − 1) + 6
anonymous
 3 years ago
Solve for x: 3(x + 1) = −2(x − 1) + 6

This Question is Closed

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.01 I think its this one 4 5 25

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.0All you have to do is distribute 3(x+1)=2(x1)+6 3x+3=2x+2+6 Add Like terms 3x+3=2x+8 add 2x on both sides +2x +2x ________________ 5x+3=8 Subtract 1 on both sides 3 3 ___________________ 5x=5 Now just divide 5 on both sides x=?

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.0So it would be 1, right?
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.